Progressive Muscular Dystrophy (Duchenne Type) (Case Report) - Soelatin Winarno; Indrawarman Indrawarman; Sabdo Waloejo; Lydia Kristianti (Indonesian Pediatric Society, 1976)
Clinical findings of two brothers suffering from progressive muscular dystrophy pseudohypertrophic type according to Duchenne are reported. Literatures dealing with its clinical classification, biochemical disturbances, hypotheses of the pathogenesis, management of treatment, mode of action of A.T.P. and the pedigree have been briefly reported. Progressive Muscular Dystrophy is a progressive disease affecting voluntary muscles; It is characterized by a decreased strength in the affected muscles with rapid or slow gradual progression. About 45% of the patients gave a history that at least another member of the family is affected by the disease. Pseudohypertrophic form (Duchenne type) is usually inherited as a recessive factor, often sexlinked.